Developing Red Chilli Downstream Business In Simalungun District - Bayu, Eva Sartini (Talenta Publisher Universitas Sumatera Utara, 2019)
This training held at Gondang Rejo Farmers Group, Bandar Huluan District, Simalungun District. The purpose of this training is (1) provide broader knowledge to farmers in handling post-harvest red chili; (2) train and guide farmers in managing red chili to become a durable food product; and (3) increasing the economic value of red chili so that farmers do not experience losses when the harvest is abundant, and the price of chili is low. Development of local commodities, especially red chili; providing training material in the process of product manufacturing and packaging; Implementation of this training is the processing of fresh red chili into powdered red chili using a simple dryer and grinder capable of producing chili powder products that have a longer shelf life and are in accordance by the standard.The outcome will developed skill abilty,built networking and encourage red chilli farmers interest to increase the amount of production for continuity the supply side. By developing the downstream red chilli it could increase the income of the red chili farmers.